Foreword - Gurgu, Elena (Annals of Spiru Haret University. Economic Series, 2016)
Economic snapshot for the major economies at the end of the first half of 2016 looks a little bit unexpected. Global growth remained tepid in the first half of 2016. An estimate produced by Focus Economics shows that the world’s GDP increased 2.4% year-on-year in Q2 2016, which followed a 2.5% rise in Q1. According to the estimate, global economic activity has been slowing uninterruptedly since Q1 2015 and Q2’s result marked the weakest rate since Q1 2013.